2013
DOI: 10.3724/sp.j.1037.2012.00264
|View full text |Cite
|
Sign up to set email alerts
|

PHASE FIELD SIMULATION OF AUTO-CATALYTIC GROWTH EFFECT OF COHERENT Ni4Ti3 PRECIPITATE IN Ni 4 Ti 3 SHAPE MEMORY ALLOY

Abstract: The precipitation behavior and distribution of Ni 4 Ti 3 particles in NiTi alloys have a significant influence on the subsequent martensitic transformation, which may consequently affect shape memory effect and superelasticity of NiTi alloys. The latest experimental studies confirmed that in single crystal NiTi alloy, the Ni 4 Ti 3 particles nucleate and grow as an autocatalytic way leading to a step-like configuration. The autocatalytic nucleation known as collective manner has been widely studied in martensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…[ 31,32 ] The energy which is needed in the process of precipitation and growth generally comes from the reduction of chemical‐free energy, relaxation of elastic energy, reduction of interfacial energy, and external energy. Ke et al [ 33 ] study the generation mechanism of autocatalytic effect of Ni 4 Ti 3 precipitates by using the phase‐field model, and found that in the initial time of simulation, to alleviate the morphological mismatch between spherical Ni 4 Ti 3 precipitates and NiTi matrix phase, the chemical‐free energy of the system gradually increased, and the elastic energy and interface energy gradually decreased. When Ni 4 Ti 3 precipitates and NiTi matrix phase are optimally matched, the chemical‐free energy gradually decreases, and the elastic energy and interfacial energy gradually increase during the phase transformation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 31,32 ] The energy which is needed in the process of precipitation and growth generally comes from the reduction of chemical‐free energy, relaxation of elastic energy, reduction of interfacial energy, and external energy. Ke et al [ 33 ] study the generation mechanism of autocatalytic effect of Ni 4 Ti 3 precipitates by using the phase‐field model, and found that in the initial time of simulation, to alleviate the morphological mismatch between spherical Ni 4 Ti 3 precipitates and NiTi matrix phase, the chemical‐free energy of the system gradually increased, and the elastic energy and interface energy gradually decreased. When Ni 4 Ti 3 precipitates and NiTi matrix phase are optimally matched, the chemical‐free energy gradually decreases, and the elastic energy and interfacial energy gradually increase during the phase transformation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, mechanical strength is also related to the grain size. [ 33 ] The finer the grain, the smaller the number of dislocations in the dislocation cluster, the smaller the stress concentration, and the higher the strength of the materials. [ 29,37 ] And it can be seen from Figure 6 that the yield strength of the S 2 sample is higher, which is due to the strengthening law of fine‐grain strengthening.…”
Section: Resultsmentioning
confidence: 99%
“…The same initial NiTi matrix composition and parameter values as those used in the above threedimensional (3D) simulation (figure 1) are set, and figure 2 shows the result of the crosssectional view of different slices along the z direction of the simulation frame. In these snapshots, it is interesting to observe several sequences with featured morphologies: (i) the variants with the same orientation organize in a step-like array, as marked by 'A' in figure 2(a); (ii) the variants with different orientations arrange in an edge-face way, as marked by 'B' in figure 2(a); (iii) the variants with the same orientation arrange in a horizontal way with a distance between them, as marked by 'C' in figures 2(b) and 2(c), where the variants in this array would coalesce and form larger precipitates [18,35], and further they may also be considered as a special type of 'B' array with zero vertical spacing between the variants. It was previously found that among these featured sequences, the step-like array owns the supreme priority, and second the horizontal array, followed by the edge-face array [35].…”
Section: Featured Morphology Of Ni 4 Ti 3 Precipitatesmentioning
confidence: 99%
“…In these snapshots, it is interesting to observe several sequences with featured morphologies: (i) the variants with the same orientation organize in a step-like array, as marked by 'A' in figure 2(a); (ii) the variants with different orientations arrange in an edge-face way, as marked by 'B' in figure 2(a); (iii) the variants with the same orientation arrange in a horizontal way with a distance between them, as marked by 'C' in figures 2(b) and 2(c), where the variants in this array would coalesce and form larger precipitates [18,35], and further they may also be considered as a special type of 'B' array with zero vertical spacing between the variants. It was previously found that among these featured sequences, the step-like array owns the supreme priority, and second the horizontal array, followed by the edge-face array [35]. It should be pointed out that these sequences of particular variants in the present study are evolved from initially randomly placed nuclei and formed by the existing and nearby nuclei; thus, they are different from those intrinsic features reported in previous work [36], which requires considering the nuclei occurrences in the surrounding region of growing precipitate, and one needs to tackle the phenomenon by considering the precipitate nucleation behaviors [37,38].…”
Section: Featured Morphology Of Ni 4 Ti 3 Precipitatesmentioning
confidence: 99%
“…In recent years, porous FSMAs and FSMA composites have attracted great interest due to their potential application in biomedical devices, shock-absorbing devices, and lightweight actuators/sensors [12][13][14][15]. Chmielus et al [16] demonstrate that the MFIS of porous Ni-Mn-Ga alloys can reach 2.0-8.7% by introducing pores smaller than grain size.…”
Section: Introductionmentioning
confidence: 99%